NOT HAVING THE FAMILY, INSURANCE, AND MONEY AND EXPERIENCING LOTS OF PAIN: FEARS ABOUT CANCER AMONG OLDER LATINO MEN. (20th December 2022) - Carrion, Iraida; Neelamegam, Malinee
Abstract: Cancer is the second leading cause of death among Latino men. A total of 44.1% of Latino males 60-years or older have a lifetime probability of developing invasive cancer with lower survival rates, even when accounting for age and stage distribution. Given the population growth is essential to examine older Latinos' understanding of a cancer diagnosis. The study consisted of 200 surveys that included a qualitative component consisting of open-ended questions in Spanish. We separately analyzed the responses of the 57 immigrant Latino men to understand their perspective regarding cancer, prevention, diagnosis, and treatment. The median age is 68 years and the length of stay in the US is 27 years. Utilizing a grounded theory approach and thematic analysis, codes were developed based on five priori interview themes: leaving people behind, worry and stress about payment, emotions of sadness and fear of uncertainty, struggle with acceptance, and faith as comfort.